1999
DOI: 10.1046/j.1365-2672.1999.00541.x
|View full text |Cite
|
Sign up to set email alerts
|

Presence of peptidase activities in different varieties of cheese

Abstract: Lactic acid bacteria (LAB) counts, PepX activity towards H‐Phe‐Pro‐βNA, and aminopeptidase activity towards H‐Arg‐βNA.HCl, H‐Lys‐βNA, H‐Leu‐βNA, H‐Pro‐βNA, H‐Glu‐βNA derivatives have been evaluated in 32 commercial samples of cheese, one processed cheese, and one yoghurt. The presence of intracellular exo‐peptidase activities in cheese extracts free from bacterial cells was detected, even after 1 year of ripening. An inverse ratio between the presence of viable lactic microflora and peptidase activity in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 12 publications
3
19
0
Order By: Relevance
“…The suspension was centrifuged (12 000 Â g for 30 min at 4 1C) and the supernatant obtained was filtered through Acrodisc s GHP membrane filters of 0.22 mm pore size (Pall, NY, USA). Cheese extract (125 mL) and substrate (125 mL; arginyl-prolyl-b-naphthylaminde 0.656 mM, and Fast Garnet 0.656 mM, in 50 mM phosphate buffer, pH 7.0) were incubated in microtiter plates at 37 1C for 10 min (Gatti, Fornasari, Mucchetti, Addeo, & Neviani, 1999). Peptidase activity was assayed at 580 nm (Sunrise photometer, Tecan GmbH, Gro¨dig, Austria) against a blank containing 125 mL of the extraction buffer instead of the cheese extract (Bouquien, Corrieu, & Desmazeaud, 1988).…”
Section: Detection Of X-prolyl-dipeptidyl-aminopeptidase (Pepx)mentioning
confidence: 99%
“…The suspension was centrifuged (12 000 Â g for 30 min at 4 1C) and the supernatant obtained was filtered through Acrodisc s GHP membrane filters of 0.22 mm pore size (Pall, NY, USA). Cheese extract (125 mL) and substrate (125 mL; arginyl-prolyl-b-naphthylaminde 0.656 mM, and Fast Garnet 0.656 mM, in 50 mM phosphate buffer, pH 7.0) were incubated in microtiter plates at 37 1C for 10 min (Gatti, Fornasari, Mucchetti, Addeo, & Neviani, 1999). Peptidase activity was assayed at 580 nm (Sunrise photometer, Tecan GmbH, Gro¨dig, Austria) against a blank containing 125 mL of the extraction buffer instead of the cheese extract (Bouquien, Corrieu, & Desmazeaud, 1988).…”
Section: Detection Of X-prolyl-dipeptidyl-aminopeptidase (Pepx)mentioning
confidence: 99%
“…Increasing levels of proteinase, endopeptidase, dipeptidase, tripeptidase activities were noted with ripening time and in general, enzyme activity was higher in the rind than in the core of the cheese. A survey of the levels of aminopeptidase and Pep X activities in extracts of 32 commercial cheeses including Swiss, Italian and Dutch types and mould or smear ripened varieties was carried out by Gatti, Fornasari, Muchetti, Addeo, and Neviani (1999). Highest aminopeptidase activity was detected against arginine, lysine b-naphtyylamide (bNA) substrates, with less activity against leucine-bNA and little or no activity against proline-b NA or glutamate-bNA: In agreement with other studies, significant Pep X activity was detected in most of the varieties surveyed, including those with extended ripening periods, such as Sbrinz, Parmigiano Reggiano and Grana Padano.…”
Section: Lactic Acid Bacteriamentioning
confidence: 99%
“…Sample extracts were prepared according to Gatti et al [17]. A dialysis step was included to eliminate any low-molecularweight substances such as salts which could interfere with the successive reactions.…”
Section: Determination Of Peptidase Activitiesmentioning
confidence: 99%
“…Residual enzymatic activity in cheese can be considered as the trace of the microbial ecosystem evolution during aging [17,40]. In a comprehensive study of the relationship between starter autolysis and the proteolytic enzyme complement released in Cheddar cheese, Sheehan et al [34] found that differences in lactococcal starter autolysis influenced the proteolytic activities of the released enzymes during ripening.…”
Section: Introductionmentioning
confidence: 99%